PENGEMBANGAN KAWASAN INDUSTRI TELEMATIKA DALAM UPAYA MENDORONG DAYA SAING REGIONAL (KASUS KOTA CIMAHI) - Lia Warlina; Rifiati Safariah; Andri Heryandi (TATALOKA, 2019)
The ICT industry is developing greatly because human dependency of information technology increases rapidly. In order to drive ICT industry competitiveness, well planned development should be carried out based on its vision. One of ICT industry cluster in Indonesia is in Cimahi City. The research objectives were to identify general characteristics of the ICT industry and its core competence, and also to acquire internal and external factors of competitiveness; and also to identify key factors that could be developed to drive regional competitiveness of ICT industry in Cimahi City. Primary data survey conducted to obtain information regarding (1) ICT industry characteristics, (2) core competence of ICT industry and (3) internal factor of competitiveness. Meanwhile, secondary data survey was conducted to obtain information regarding external factors of competitiveness. A prospective analysis was conducted to build a scenario in developing ICT industry cluster in Cimahi City. Research result showed that the core competence of ICT industry was animation, film and information system. Key factors to drive regional competitiveness of ICT industry cluster were (1) telecommunication service quality; (2) skilled labor availability; (3) responsiveness on change and innovation; (4) business ethics and (5) ICT industry regulation.